PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL DI KABUPATEN/KOTA PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2015-2019 - Marni Marni; Alean Kistiani Hegy Suryana; Yunita Niqrisah Dwi Pratiwi (Universitas Boyolali, 2022)
Every region in Indonesia is given the right to manage regional autonomy in accordance with Law No. 32 of 2004. PAD is one of the most important incomes for a region. The potential sector that can be extracted from PAD is the tourism sector which has a contribution to regional taxes through restaurant taxes, entertainment taxes, and hotel taxes. This study aims: 1) Knowing and partially testing the effect of Regional Taxes, Regional Retribution and Balancing Funds on Capital Expenditures in Regency and City Governments in the Province of DIY in 2015-2019. 2) Knowing and testing the simultaneous effect of Regional Taxes, Regional Levies and Balancing Funds on Capital Expenditures in Regency and City Governments in the Province of DIY in 2015-2019. This research embodies the type of quantitative research with causal comparative or ex post facto. The subject of this research is the Province of DIY for the 2015-2019 period. The data used is secondary data originating from the Regional Financial Statistics of the 2015-2019 APBD Realization Report. The data collection system uses documentation and literature study methods. The analytical method used is descriptive statistical analysis, classical assumption test and multiple linear regression analysis. The results of this study are: 1) Local Taxes have an insignificant effect on Capital Expenditures in the Province of DIY 2) Regional levies have a non-significant effect on Capital Expenditures in the Province of DIY 3) Balanced Funds have a significant effect on Capital Expenditures in the Province of DIY 4) Found an effect positive and significant Regional Taxes, Regional Levies and Balancing Funds together on Capital Expenditures in the Province of the Special Region of Yogyakarta.